Design and Implementation of Intelligent Monitoring System for Brake Shearing Machine. (February 2019) - Wang, Yong; Zhu, Jiamin; Chen, Sheng; Yu, Jun; Chen, Dabing
Abstract: In order to obtain the working state of the brake shearing machine, the paper proposed a monitoring system designed for the key data of the shearing machine such as the throat deformation, the temperature of the shearing cylinder and the vibration of the upper tool holder. The selection and connection of the hardware and the method of setting up the wired and wireless networks of the monitoring system are specified first in this paper. Then the methods of data acquisition and processing are put forward. Finally the functions of the host computer and the cloud server as well as the structure of the software are illustrated in detail. The monitoring system is suitable for the production line which contains many sheet metal machine tools, and it is of reference significance to establish a larger range of machine tool monitoring system.